THE IMPORTANCE OF TIME MANAGEMENT FOR STUDENTS - Safarova Dildora,; Choryorqulova Shahzoda,; Yaxshilikova Farangiz,; Maqsudova Afifaxon, (PEDAGOGS, 2025)
Annotation: This article explores the significance of time management for students. Effective time management plays an essential role in improving academic performance, reducing stress, and achieving personal goals. The article discusses the benefits of time management, the common challenges students face, and practical strategies for organizing their time efficiently. Additional insights on the psychological impact of time management and real-life student experiences are also provided.